Abdominal cocoon accompanied by multiple peritoneal loose body. Issue 9 (March 2017) - Cheng, Yongyuan; Qu, Lintao; Li, Jun; Wang, Bin; Geng, Junzu; Xing, Dong
Abstract: Rationale: Abdominal cocoon and peritoneal loose body are both rare abdominal diseases. Patient concerns: The patient reported in this case was a 47-year-old man who suffered from abdominal pain and distension for 3 days. Diagnosis: X-ray, computed tomography, and magnetic resonance imaging revealed multiple peritoneal loose body and small bowel obstruction, characterized by a total encapsulation of the small bowel with a fibrous membrane. Interventions: The patient underwent surgical treatment and exploratory laparotomy confirmed the diagnosis of abdominal cocoon. Outcomes: Histopathological examination of pelvic nodules confirmed peritoneal loose body. Lessons: To our knowledge, the herein reported case is the first abdominal cocoon that was accompanied by multiple peritoneal loose body.